2018
DOI: 10.3233/jin-170054
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological parameters in quantitative prediction of treatment outcome in schizophrenic patients

Abstract: The aim of the study was to reveal the set of neurobiological parameters informative for individual quantitative prediction of therapeutic response in schizophrenic patients. Correlation and regression analyses of quantitative clinical scores (by Positive And Negative Syndromes Scale - PANSS), together with background EEG spectral power values and four immunological parameters: enzymatic activity of leukocyte elastase and of alpha-1 proteinase inhibitor, as well as serum levels of autoantibodies to common myel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
1
0
3
Order By: Relevance
“…In that sense QEEG markers could be used to individualize treatment and studies showed promising results for instance in depression, 36,37 obsessive-compulsive disorder, 38 anxiety disorders, and schizophrenia albeit the meta-analyses did not show any consistency. 39,40 With regard to ADHD, various studies emphasized that the increase in theta power and theta/beta ratio and the decrease in beta power can be a useful tool for the diagnosis of ADHD. 21,23,41,42 On the other hand, Arns et al 17 established that theta/beta ratio cannot be a reliable assessment tool for the diagnosis of ADHD but it can be applied as a tool, which may help monitor the prognosis in only 1 subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…In that sense QEEG markers could be used to individualize treatment and studies showed promising results for instance in depression, 36,37 obsessive-compulsive disorder, 38 anxiety disorders, and schizophrenia albeit the meta-analyses did not show any consistency. 39,40 With regard to ADHD, various studies emphasized that the increase in theta power and theta/beta ratio and the decrease in beta power can be a useful tool for the diagnosis of ADHD. 21,23,41,42 On the other hand, Arns et al 17 established that theta/beta ratio cannot be a reliable assessment tool for the diagnosis of ADHD but it can be applied as a tool, which may help monitor the prognosis in only 1 subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…Материалы фундаментальных исследований в области нейробиологии, а также данные собственных клинико-биологических разработок [31][32][33][34][35][36] позволяют выдви-нуть следующее положение: формирование как позитивной, так и негативной симптоматики, выступающей в клиническом пространстве шизофрении, происходит в рамках единого процесса -нейровоспаления.…”
Section: Informatiom About Authorsunclassified
“…Dolayısıyla bu dalgacık dönüşümü işlemi, incelenmek istenen frekans aralığına göre belirlenen kesikli pozitif α değerleri kullanılarak ölçeklendirilip kesikli formdaki x(t) sinyalinin her bir noktalarından başlatılmasıyla elde edilen α × τ sayıdaki φ * ( − τ α ) fonksiyonu ile kesikli x(t) sinyalinin her bir kesikli zaman anında çarpılıp toplanması yoluyla gerçeklenmektedir. Literatürde EEG sinyalleri 4 temel alt frekans bandına ayrılmakta ve bu dalgalar delta (0,5-3 Hz), teta (4-7 Hz), alfa (8)(9)(10)(11)(12)(13), beta (14-30 Hz) dalgaları olarak adlandırılmaktadır. Önerilen bu çalışmada bu alt frekans bantlarının dördünün de ayrı ayrı incelenmesi amaçlandığından, çalışmada 0.5-30 Hz (Delta başlangıcı -Beta bitişi) arası frekanslara odaklanılmıştır.…”
Section: Eeg Kayıtlarının Analiziunclassified
“…Bu nedenlerden dolayı EEG sinyallerinden maksimum bilgiyi edinebilmek için bilgisayar ortamında EEG verilerini analiz eden çalışmalar yapılmakta ve başta Fourier dönüşümü, dalgacık dönüşümü ve yapay sinir ağları olmak üzere farklı nicelleştirme yöntemleri kullanılmaktadır. Bu yöntemler aracılığıyla nicelleştirilen EEG verilerinden deliryum [2], depresyon [3], epilepsi [4], [5], Alzheimer [6], [7], travmaya bağlı beyin hasarı [8], şizofreni [9], çocuklarda dikkat eksikliği ve hiperaktivite [10], [11] gibi sinir sistemi ile ilişkili hastalıklarda beyin dinamiğinde meydana gelen değişikliklere ilişkin kapsamlı bilgi edinilebilmektedir.…”
Section: Introductionunclassified